Understanding of Al-Jibt (Magic) in The Perspective of Hadith - Heri, Heri; Nashirulhaq, Nashirulhaq; Kadiatmaja, Agung Pranoto (Jurnal Multidisiplin Ibrahimy, 2026)
In the modern digital era, practices reminiscent of pre-Islamic Jahiliyyah culture-such as shamanism, supernatural rituals, and various forms of divination-have reemerged and become increasingly prominent through television broadcasts and social media platforms. This phenomenon raises significant concerns about its potential influence on Islamic faith and the spiritual integrity of Muslim communities. This research seeks to reexplore the notions of al-jibt and al-thaghut from a Hadith-based perspective, underscoring their relevance in responding to the widespread revival of occult-related activities in contemporary society. Adopting a qualitative research design with a thematic analytical framework, this study utilizes takhrij al-hadith to trace and assess chains of transmission and applies sharḥ al-hadith to interpret the meanings and contextual implications of the examined narrations. The data were gathered through comprehensive library research, concentrating on Hadith sources from Kutub al-Sittah and authoritative commentaries, complemented by digital resources such as Maktabah Shamilah. The findings reveal that many Hadiths addressing al-jibt—including acts such as ‘iyafah (seeking omens from birds), ṭiyarah (pessimistic superstitions), and al-thuruq (divination using lines or stones)—contain weak (ḍa‘if) transmission chains. Nevertheless, the existence of multiple supporting isnād routes alleviates the degree of this weakness, thereby strengthening the Hadiths’ usability in explaining unlawful forms of magic. Further matan analysis confirms that these practices are categorized as prohibited, deceptive, and often linked to satanic manipulation. The discussion emphasizes that these Hadiths maintain strong relevance in confronting modern expressions of occultism, such as contemporary shamanic services, spirit-medium consultations, astrology, talisman usage, and paranormal content propagated through mass media. Although their outward forms may differ from those of the past, the core elements remain consistent with what the Hadith condemns: dependence on powers other than Allah and deviation from the principles of pure monotheism. Consequently, a sound understanding of al-jibt is essential for enhancing Muslim awareness and safeguarding the community from the persistence of misguided supernatural beliefs in the modern world.